The place of Algerian auditing standards in the audit mission - abdesselam, Walid; benfradj, zouina (Journal of Research in Finance and Accounting, 2023)
The aim of this study is to know the place of the Algerian auditing standards in the audit mission, starting from Accepting the mission until the issuance of the report. This study cocluded that the Algerian auditing standards meet the needs of the auditors in Algeria if the appropriate enivrement is provided for their application, The Algerian auditing standards issued can be applied in all stages of the audit mission, Through this study, we propose to expedite the issuance of the rest of the Algerian auditing standards.